Growth, crystal structure, and properties of epitaxial BiScO3 thin films - Takayama-Muromachi, Eiji (2011)
Epitaxial thin films of BiScO3—a compound thermodynamically unstable under ambient conditions—were grown on BiFeO3-buffered SrTiO3 substrates. X-ray diffraction confirmed the reasonable crystalline quality of the films with a full width at half maximum of 0.58° in ω (004 reflection), 0.80° in ϕ (222 reflection), and 0.28° in θ. The epitaxial thin films of BiScO3 on SrTiO3 retain the principal structural features of bulk BiScO3 (i.e., octahedral tilting and the pattern of Bi displacements) that give rise to a pseudo-orthorhombic unit cell 2√2acX√2acX4ac (ac≈4 Å refers to the lattice parameter of an ideal cubic perovskite). Films grown on {100} substrates adopt the bulk monoclinic structure, whereas films on the (110) substrates appear to exhibit an orthorhombic symmetry. The dielectric permittivities were modest (≈30) with low loss tangents (<1% at low fields); no maxima were observed over a temperature range of −200 to +350 °C. There is no evidence of significant hysteresis (either ferroelectric or antiferroelectric) at room temperature up to the breakdown strength of the films.